Dopaminergic Nigrostriatal Connectivity in Early Parkinson Disease: In Vivo Neuroimaging Study of 11C-DTBZ PET Combined with Correlational Tractography - Sanchez-Catasus, Carlos A; Bohnen, Nicolaas I; Yeh, Fang-Cheng; D'Cruz, Nicholas; Kanel, Prabesh; Müller, Martijn L T M (The Journal of nuclear medicine (1978), 2021)
Previous histopathologic and animal studies have shown axonal impairment and loss of connectivity of the nigrostriatal pathway in Parkinson disease (PD). However, there are conflicting reports from in vivo human studies. 11C-dihydrotetrabenazine (11C-DTBZ) is a vesicular monoamine type 2 transporter PET ligand that allows assessment of nigrostriatal presynaptic dopaminergic terminal integrity. Correlational tractography based on diffusion MRI can incorporate ligand-specific information provided by 11C-DTBZ PET into the fiber-tracking process. The purpose of this study was to assess the in vivo association between the integrity of the nigrostriatal tract (defined by correlational tractography) and the degree of striatal dopaminergic denervation based on 11C-DTBZ PET. Methods: The study involved 30 subjects with mild to moderate PD (23 men and 7 women; mean age, 66 ± 6.2 y; disease duration, 6.4 ± 4.0 y; Hoehn and Yahr stage, 2.1 ± 0.6; Movement Disorder Society [MDS]–revised Unified Parkinson Disease Rating Scale [UPDRS] [I–III] total score, 43.4 ± 17.8) and 30 control subjects (18 men and 12 women; mean age, 62 ± 10.3 y). 11C-DTBZ PET was performed using standard synthesis and acquisition protocols. Correlational tractography was performed to assess quantitative anisotropy (QA; a measure of tract integrity) of white matter fibers correlating with information derived from striatal 11C-DTBZ data using the DSI Studio toolbox. Scans were realigned according to least and most clinically affected cerebral hemispheres. Results: Nigrostriatal tracts were identified in both hemispheres of PD patients. Higher mean QA values along the identified tracts were significantly associated with higher striatal 11C-DTBZ distribution volume ratios (least affected: r = 0.57, P = 0.001; most affected: r = 0.44, P = 0.02). Lower mean QA values of the identified tract in the LA hemisphere associated with increased severity of bradykinesia sub-score derived from MDS-UPDRS part III (r = −0.42; P = 0.02). Cross-validation revealed the generalizability of these results. Conclusion: These findings suggest that impaired integrity of dopaminergic nigrostriatal nerve terminals is associated with nigrostriatal axonal dysfunction in mild to moderate PD. Assessment of nigrostriatal tract integrity may be suitable as a biomarker of early- or even prodromal-stage PD.